Inlislite Evaluation in the Processing of Library Materials Toward Usability Model - Putri, Indira Adiadwi; RA, Okta Reni Azrina; Kesuma, Aghesna Rahmatika; Iqbal, Rahmat (Jurnal El-Pustaka, 2023)
An information system can ease the user in receiving information.  The library needs to use effective and efficient service by using the information system. Processing of library materials is important to do to facilitate the search for information and expedite service activities. This research has a case study at the Bandar Lampung City Library and Archives Service which has used the INLISLite system since 2014. But until now they are still using INLISLite version 3.1. This study uses a qualitative descriptive method by conducting field research on the problems that occur, as well as interacting directly with librarians. INLISLite version 3.1 which is used displays several menus such as Back Office, Read on Place, Guest Book, Online Membership, Digital Collection Services, OPAC, Articles, Member Registration, Statistics, Surveys, Self-Returns, and Self Borrowing. The results first result from the study, librarians can process library materials on the Back Office menu. The second is there are no problems in the learnability and efficiency aspects because in this aspect the INLISLite system makes it very easy for librarians, but there are problems in the Memorability, Error, and Satisfaction aspects.